Experiences of health information-seeking among patients with cancer in China: a qualitative study - Wu, Yanjun; Li, Shenglu; Zhou, Yan; Duan, An; Zhuo, Qiqi (Frontiers in Public Health, 2025)
PurposeAlthough information provision improves physical and psychological well-being, few studies have evaluated Chinese cancer patients’ information needs. Our study aimed to explore the health information-seeking experiences of Chinese cancer patients, focusing on their needs, preferences, and cultural influences. This will inform the development of culturally sensitive and patient-centered information provision strategies.MethodsSemi-structured face-to-face, in-depth interviews were conducted with 17 cancer patients. Participants were recruited in one oncology unit in China from November 2023 to February 2024. Interviews were audio-recorded, transcribed by two researchers, evaluated using conventional content analysis, and translated.ResultsFour themes and eleven categories emerged from the qualitative data: passively received information (let nature take its course, maintain harmonious relationships); seeking emotional support (seeking positive stories, encouragement from healthcare professionals, family members’ involvement); different roles of information (reassuring, troublesome, difficult truths) and optimal way to obtain information (plain language, individualized, trust in the doctor most).ConclusionThe influence of culture on patients’ information needs is inevitable. In China, healthcare professionals should encourage patients with cancer to express their information needs in order to develop health information provision strategies tailored to their needs. Notably, emotional support helps maintain psychological well-being. Family members’ involvement in information-seeking progress is also an important component of emotional support. Information provision should be individualized and aligned with the patients’ information-seeking styles and individual differences. Furthermore, healthcare professionals must use plain language, provide accurate information, and correctly guide patients on online information-seeking.